Information System Project Development Management Ratio Set Assy GP Using Scrum Method - Muchammad Abdulloh Munib; Ahmad Luthfi (Journal of Information System and Informatics, 2023)
In April 2011, the term Industry 4.0 was introduced at the Hannover Fair. PT Yamaha Indonesia was an early adopter, implementing it in their piano manufacturing process. To achieve production targets, it is necessary to monitor the production series, including the assembly of piano components into a complete unit. SAP, a software platform, is used to improve efficiency, with one of its modules being K-STAFF, which has four derivative applications: K-Master, K-Ticket, K-Score, and K-Tiptop. However, the current production process is monitored through scanning input using a SAP derivative application, which is not visualized in the production area, leading to failed targets. To address this issue, a system is required to visualize input scan results to enable direct monitoring of the production process and achieve production targets. As a result, PT Yamaha Indonesia developed the Ratio Set Assy Grand Piano system using the SCRUM method. This system includes an MIS that monitors the ratio set of piano, visualized with Apache E-Charts, manages planning, and identifies priority spare parts in real-time. This research contributes to the development of a more efficient and effective production process